2022
DOI: 10.1155/2022/5935353
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Exercise Intervention on Internet Addiction and Autonomic Nervous Function in College Students

Abstract: Objective. To investigate the effects of 12-week physical exercise (jogging, basketball, and outdoor training) on sleep quality, harmful mood, and heart rate variability (HRV) in college students with Internet addiction. Methods. 46 college students with Internet addiction were chosen and then randomly assigned to the Internet addiction group (IA, n = 23 ) and the Internet addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…In this study, 29.5% of the students had poor sleep quality, which was lower than that of Stanford University (42.4%) ( 32 ). The overall PSQI score was 4.35, which was similar to the results of South Korea (4.21) ( 33 ), lower than the results of Japanese nursing students (6.86) ( 34 ), lower than the results of Anhui province (5.37) ( 35 ) and Beijing (5.38) ( 13 ).…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, 29.5% of the students had poor sleep quality, which was lower than that of Stanford University (42.4%) ( 32 ). The overall PSQI score was 4.35, which was similar to the results of South Korea (4.21) ( 33 ), lower than the results of Japanese nursing students (6.86) ( 34 ), lower than the results of Anhui province (5.37) ( 35 ) and Beijing (5.38) ( 13 ).…”
Section: Discussioncontrasting
confidence: 53%
“…This leads to the conclusion that positive movement “addiction” may replace the Internet (cell phones, computers). Rather than a deliberately suppressed negative “addiction,” the displacement is derived from the channel of instinct, transfer, and exchange [ 41 , 44 , 45 , 46 ]. The results also showed that different intensity exercise levels had different effects, and moderate-intensity exercise was better than low-intensity and high-intensity exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis shows that exercise adherence can play an intervention role in college students’ internet addiction ( Wu et al, 2018 ). An intervention experimental study showed that long-term physical exercise can significantly reduce the degree of college students’ internet addiction ( Zhang and Xu, 2022 ). From the perspective of biological mechanism, physical exercise can change the content of some neurotransmitters in the body, such as dopamine, 5-hydroxytryptamine and other monoamines as well as endorphins.…”
Section: Introductionmentioning
confidence: 99%